Maintained barostatic regulation of heart rate in digesting snakes (Boa constrictor) - Wang, Tobias; Abe, Augusto S.; Cruz-Neto, Ariovaldo P.; Andrade, Denis V.; Taylor, Edwin W. (The Company of Biologists, 2021)
When snakes digest large meals, heart rate is accelerated by withdrawal of vagal tone and an increased non-adrenergic-non-cholinergic tone that seems to stem from circulating blood-borne factors exerting positive chronotropic effects. To investigate whether this tonic elevation of heart rate impairs the ability for autonomic regulation of heart during digestion, we characterised heart rate responses to pharmacological manipulation of blood pressure in the snake Boa constrictor through serial injections of sodium nitroprusside and phenylephrine. Both fasting and digesting snakes responded with a robust tachycardia to hypotension induced by sodium nitroprusside, with digesting snakes attaining higher maximal heart rates than fasting snakes. Both fasting and digesting snakes exhibited small reductions of the cardiac chronotropic response to hypertension, induced by injection of phenylephrine. All heart rate changes were abolished by autonomic blockade with the combination of atropine and propranolol. The digesting snakes retained the capacity for compensatory heart rate responses to hypotension, despite their higher resting values, and the upward shift of the barostatic response curve enables snakes to maintain the cardiac limb of barostatic regulation for blood pressure regulation.
Keywords: Autonomic control; Baroreception; Blood pressure; Cardiovascular; Nitroprusside; Phenylephrine; Reptile; Snake